2023
DOI: 10.7554/elife.80040
|View full text |Cite
|
Sign up to set email alerts
|

RNA localization mechanisms transcend cell morphology

Abstract: RNA molecules are localized to specific subcellular regions through interactions between RNA regulatory elements and RNA binding proteins (RBPs). Generally, our knowledge of the mechanistic details behind the localization of a given RNA is restricted to a particular cell type. Here, we show that RNA/RBP interactions that regulate RNA localization in one cell type predictably regulate localization in other cell types with vastly different morphologies. To determine transcriptome-wide RNA spatial distributions a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 93 publications
2
13
0
Order By: Relevance
“…We found a large overlap between the transcripts present at the periphery of both glia and neurons (Figure 1D). Our observations agree with a recent study highlighting conserved mRNA transport mechanisms between cell types (Goering, Arora and Taliaferro, 2022) and significant overlap of localized transcripts within astrocytes, radial glia and neurons (D’Arcy and Silver, 2020).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We found a large overlap between the transcripts present at the periphery of both glia and neurons (Figure 1D). Our observations agree with a recent study highlighting conserved mRNA transport mechanisms between cell types (Goering, Arora and Taliaferro, 2022) and significant overlap of localized transcripts within astrocytes, radial glia and neurons (D’Arcy and Silver, 2020).…”
Section: Resultssupporting
confidence: 93%
“…Certainly, the glial sub-types we characterized in Drosophila at the NMJ are also present, as defined by specific cell type markers, in association with neurons and synapses in the central brain. Furthermore, recent studies suggest that mRNA localization in one cell type mediated by interactions with RBPs can be predictive of the same interactions and localizations in other cell types with very different morphologies and functions (Goering, Arora and Taliaferro, 2022). It has also been shown that radial glia, astrocytes, and neurons, all of which have quite distinct morphologies and functions, share a significant overlap in the types of mRNAs localized to their protrusions (D’Arcy and Silver, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We next sought to identify specific cis-elements (LEs) within MBsome-localized RNAs that regulated their trafficking to the MB. We recently identified RNA elements that were necessary and sufficient for transport to both the neurites of neuronal cells and the basal pole of epithelial cells ( Goering et al, 2023 ). Both of these subcellular locations are associated with the plus ends of microtubules and we showed that these RNA elements directed RNAs to their destinations by targeting them to microtubule plus ends.…”
Section: Resultsmentioning
confidence: 99%
“…Using data from human intestinal epithelial cells ( Goering et al, 2023 ), we then compared enrichments across the apicobasal axis for MBsome RNAs and all other detected RNAs. Again, we found that MBsome-enriched RNAs were significantly enriched at the basal pole of these cells compared to non-MBsome-enriched RNAs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We do not observe any correlation between change in mRNA half-lives with either length of 5′TOP motif or the presence of a PRTE in the 5′UTR, suggesting that the position of the pyrimidines directly adjacent to the cap is necessary for this effect on mRNA stability. LARP1 was shown to promote the localization of ribosomal mRNAs in a PRTE-dependent manner but did not require the stricter 5′ TOP motif, suggesting that LARP1’s interaction with ribosomal mRNAs and its functional consequence could be context dependent ( 54 ).…”
Section: Discussionmentioning
confidence: 99%